2015
DOI: 10.1080/15440478.2014.919892
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Design and Method of Creating Wicking Channels on Moisture Management and Air Permeability of Cotton Fabrics

Abstract: Garments made from cotton fabrics can readily absorb perspiration during strenuous activities but give poor performance in terms of wicking and evaporation of the perspiration, resulting in wet sticky feeling to the wearer. The aim of this study was to investigate the effect of design and method of creating wicking channels on the moisture management and air permeability of cotton fabrics. The fabric specimens were printed with hydrophobic fluorocarbon finish using four different print designs, each with two d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
23
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(24 citation statements)
references
References 9 publications
1
23
0
Order By: Relevance
“…Wang et al reported that hydrophobic-to-hydrophilic gradient across the thickness of a fabric can guide directional water-transport from the hydrophobic side to the hydrophilic side, but no water transport takes place in the opposite direction unless an extra force is applied [18,19]. Such unidirectional water penetration phenomenon was also reported by our group [20] and referred to as "water diode" [21,22] or "directional wicking" [1,23].…”
Section: Introductionsupporting
confidence: 55%
“…Wang et al reported that hydrophobic-to-hydrophilic gradient across the thickness of a fabric can guide directional water-transport from the hydrophobic side to the hydrophilic side, but no water transport takes place in the opposite direction unless an extra force is applied [18,19]. Such unidirectional water penetration phenomenon was also reported by our group [20] and referred to as "water diode" [21,22] or "directional wicking" [1,23].…”
Section: Introductionsupporting
confidence: 55%
“…[23][24][25][26][27][28][29][30] Our previous works have reported the preparation of hydrophobic-to-hydrophilic gradient fabrics that can guide directional water-transport from the hydrophobic to the hydrophilic side. In research literatures, the directional water transport was also termed "one-way water transport," "directional wicking," [33][34][35] or "water diode." In research literatures, the directional water transport was also termed "one-way water transport," "directional wicking," [33][34][35] or "water diode."…”
mentioning
confidence: 99%
“…One of the most important function of a wound dressing is its ability to absorb fluid from a highly exuding wound maintaining a moist environment in a dry wound [60]. It is clear that high chitosan concentrations significantly reduce the absorptive capacity of cotton gauze.…”
Section: Water Uptakementioning
confidence: 99%